Pediatric Kidney Transplantation: Kids are Different (Iranian Journal of Kidney Diseases, 2013)
The pediatric kidney transplant recipient differs from the adult recipient in many ways, including immune responsiveness, drug metabolism and clearance, perfusion of transplanted organs, and risk for posttransplant lymphoproliferative disease. Pediatric patients also have special quality of life issues such as cosmetic side effects of medications, stunted growth and sexual maturation, and separation from their peers. Congenital urological anomalies and glomerulosclerosis are the most common causes of pediatric end-stage renal disease. In the pediatric patients, consideration for preemptive transplantation should be first and arteriovenous fistula placement second. Pediatric patients should receive priority for kidneys from deceased donors to shorten the wait time for transplant. Fevers or changes in blood pressure may identify allograft dysfunction weeks before changes in creatinine occur. Thus, monitoring serum creatinine level is a poor indicator of allograft dysfunction in this setting. There is great concern about nonadherence to immunosuppressive therapy as children reach the stage of adolescence. This report highlights these and other important differences in the evaluation and management of the pediatric kidney transplant recipients compared with the adult and provides practical guidance to the practitioners involved in caring for such patients.